Pengenalan Konsep Buffer Zone di Desa Teluk Sinar, Kabupaten Hulu Sungai Utara: Introducing Buffer Zone Concept in Teluk Sinar Village, North Hulu Sungai Regency - Nurlaila Nurlaila; Nukhak Nufita Sari; Ronny Mulyawan; Hikma Ellya; Rila Rahma Apriani; Said Muhammad Saman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
A buffer zone is an area designated to protect a conservation area from being disturbed by the surrounding environment. The concept of a buffer zone can be adopted to protect an area or land from contamination by factories, household, and agricultural waste. Teluk Sinar Village is a village located in a freshwater swamp area where there are mines around this area. Further, agricultural practices in the area still use chemicals that leave residues and can pollute the environment, including water pollution. The problem partner is the low level of knowledge about the impact of water pollution on organisms, including human health. Through this community service, it will be a solution to understanding the effects of water pollution for members of the Bunga Seroja Farmer Group through the concept of buffer zone technology. The community service was conducted by the lecture method and gave a pocket book. It significantly increases the knowledge and understanding of farmers about the buffer zone concept.